Generation Z Undergraduate Social Work Students' Knowledge of and Attitudes Toward Older Persons: Implications for Professional Training. Issue 1 (17th February 2020) - Geyer, Stephan; Louw, Liebie
ABSTRACT: Appropriate gerontological social work services are, amongst others, dependent on social workers' knowledge of and attitudes toward older persons. The current cohort of students, known as Generation Z, are global citizens. This study determined and described South African undergraduate social work students' knowledge of and attitudes toward older persons. A cross-sectional survey was undertaken with B Social Work students ( N  = 395) at two universities. Data collection included the three scales of Palmore's First Facts of Aging Quiz in multiple-choice format (1996) and four scales of Fraboni's Scale of Agism (1990). Age and five categorical factors were considered to determine their simultaneous impact on each of the seven scales/subscales of the two instruments by performing multi-way ANOVA models. An unexpected finding was that the factor 'completed a course in gerontology' did not have any impact on any scale. Year level of study, area of childhood residence and consideration to work exclusively with older persons after graduation simultaneously impacted respondents' 'overall attitude' toward older persons. Two factors (i.e., year level of study and area of childhood residence) mutually impacted respondents' 'overall knowledge' of aging. Recommendations for the training of Generation Z students are offered concerning course content and pedagogical interventions.